AVALIAÇÃO DA CAPACIDADE DE POLIMERIZAÇÃO E ELEVAÇÃO DE TEMPERATURA PRODUZIDA POR APARELHOS FOTOPOLIMERIZADORES - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
This study evaluated the curing efficiency and the temperature increasement produced by curing units during the photo-activation of the composite, Filtek™Z250 (3M ESPE) and Filtek™Z350 (3M ESPE). At the same time, the emission spectrum and power of the curing units were tested using the spectrometer USB2000 (Ocean Optics) and the Power Meter (Ophir). The light intensity was determined by the reason between power and active top light area of each unit. The curing units used were a halogen lamp Optilux 401 (Demetron) and three light emitting diode devices (LED), LEDemetron I (Kerr), Bluephase (Ivoclar Vivadent) and Elipar Freelight (3M ESPE), with light intensity of 661 mW/cm2, 627 mW/cm2, 1229 mW/cm2 and 330 mW/cm2, respectively. The curing efficiency was evaluated by Vickers hardness, determined on bottom surface the specimens prepared in steal mold, which it was filled with the selected composite, and stored during a period of 24 hours. Using a thermocouple type-K, placed under a dentin disk with 0,5 mm thickness, it was observed The temperature increasement produced by the four devices was measured during the photo-activation of the adhesive system and of an increment of 2 mm of thickness of composite, which were activated for 20 and 40 seconds, respectively. The results of Vickers hardness and of temperature increasement were submitted to the statistical analysis ANOVA 2 way and post test Bonferroni with 5% significance. For the composite Filtek™Z250 (3M ESPE) the four units curing devices assessed did not present statistical differences in the superficial hardness. For the composite Filtek™Z350 (3M ESPE), the unit curing Elipar Freelight (3M ESPE) produced statistical lower hardness (p < 0,05), whereas it has not statistical differences in hardness among the units curing devices. The composite Filtek™Z250 (3M ESPE) presented higher hardness than resin Filtek™Z350 (3M ESPE) (p <0,05). The unit curing light emitting diode Bluephase (Ivoclar Vivadent) and the unit curing of halogen lamp Optilux 401 (Demetron) emitted the same temperature increasement statistically, reaching (17,6°C), duri ng the photo-activation of the adhesive system. The lower value of temperature increase was registered for the unit curing Elipar Freelight (3M ESPE) in the adhesive system (7,2°C) (p < 0,001) and in the composite (3,1°C) (p < 0,05). Statistically, th e temperature increasement registered during the activation of the composite was lower than the temperature increasement registered during the activation in the adhesive system (p < 0,001).
Curing efficiency and temperature increasement produced by photo-activation devices
Keywords: dureza; densidade de potência; temperatura; hardness; potential Density; Temperature; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA